2020
DOI: 10.1175/bams-d-19-0188.1
|View full text |Cite
|
Sign up to set email alerts
|

The Extended-Range Tornado Activity Forecast (ERTAF) Project

Abstract: Large-scale weather patterns favorable for tornado occurrence have been understood for many decades. Yet prediction of tornadoes, especially at extended lead periods of more than a few days, remains an arduous task, partly due to the space and time scales involved. Recent research has shown that tropical convection, sea surface temperatures, and the Earth-relative atmospheric angular momentum can induce jet stream configurations that may increase or decrease the probability of tornado frequency across the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To date, many forecasting models struggle with predictivity below 10 days [36]. Gensini et al [37], found that forecast skills are higher between two-versus three-week lead-time. Robertson et al [38], developed calibrated probabilistic forecasts for northern India up to two weeks.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many forecasting models struggle with predictivity below 10 days [36]. Gensini et al [37], found that forecast skills are higher between two-versus three-week lead-time. Robertson et al [38], developed calibrated probabilistic forecasts for northern India up to two weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that data from the instrument improved hurricane track and intensity forecasts (Schmit et al, 2009;Liu and Li, 2010;Zheng et al, 2015;Lee et al, 2017;Wang et al, 2017) and severe storm prediction (Li et al, 2011;Iturbide-Sanchez et al, 2018;Gensini et al, 2020;Wang et al, 2020) (See NOAA NESDIS (2020) for a more complete description of the OSE/OSSE process and a detailed description of these findings). These studies gave us a starting point for identifying outcomes that could be affected by the provision of sounding data and the potential magnitude of improvements.…”
Section: Observing System Experimentsmentioning
confidence: 99%
“…Although the degree of improvement has not yet been determined, the savings associated with reducing these delays by 0.2 to 0.5 percent are equal to the cost of the instrument (corresponding to 3 percent and 7 percent discount rates, respectively). OSSEs for severe storms tend to focus on individual events (Li et al, 2011;Iturbide-Sanchez et al, 2018;Gensini et al, 2020;Wang et al, 2020) making direct comparisons difficult. However discussions with experts in the industry suggest that this magnitude of improvement is achievable, and has been realized in similar cases.…”
Section: Findings Scenario 1-aviation Weathermentioning
confidence: 99%
“…Prediction of tornadoes at extended lead times of more than a few days remains an arduous task (Gensini et al 2020, Miller et al 2020. To extend the lead time of tornado forecast, a substantial body of studies has been devoted to investigating the favorable environments of tornadoes at sub-seasonal to seasonal (S2S) timescales, which has advanced our understanding of the climate signals conducive to the U.S. tornado outbreaks (Tippett et al 2015).…”
Section: Introductionmentioning
confidence: 99%